2023
DOI: 10.25304/rlt.v31.2944
|View full text |Cite
|
Sign up to set email alerts
|

University students’ perceptions of interactive response system in an English language course: a case of Pear Deck

Abstract: Pear Deck is one interactive response system that has gained popularity in recent years. This study addressed the gap in the literature and considered students’ experience of the platform in a Thai university context. This was a mixed-method study in which 320 students completed a survey including closed and open-ended components. Quantitative data measuring students’ perceptions using Likert-scale surveys were collected, while qualitative data were used to get a deeper understanding of students’ experience in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
0
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 24 publications
0
0
0
Order By: Relevance
“…Importantly, Quizizz AI may have the potential to address one of the major challenges in independent learning: students' procrastination. Many students frequently procrastinate important learning and studying duties, even though they are aware that this delay would have negative consequences for them (Anggoro & Pratiwi, 2023;Steel & Klingsieck, 2016). Rozental et al (2022) believed that procrastination negatively impacts students' academic achievements and well-being.…”
Section: Data-driven Insights Represent An Additional Advantage the P...mentioning
confidence: 99%
“…Importantly, Quizizz AI may have the potential to address one of the major challenges in independent learning: students' procrastination. Many students frequently procrastinate important learning and studying duties, even though they are aware that this delay would have negative consequences for them (Anggoro & Pratiwi, 2023;Steel & Klingsieck, 2016). Rozental et al (2022) believed that procrastination negatively impacts students' academic achievements and well-being.…”
Section: Data-driven Insights Represent An Additional Advantage the P...mentioning
confidence: 99%
“…As a matter of fact, combining the use of technology with instructions has been found to be effective (Sengsri & Anggoro, 2021). It also has been found that the use of technology such as interactive response systems in English language classrooms improved students' achievement, interest, and self-efficacy (Anak Yunus & Hua, 2021;Anggoro & Pratiwi, 2023). Using technological devices in the classroom offers a huge potential as they are easy to use with interesting features such as mobile phone applications (Zhang, 2013).…”
Section: Introductionmentioning
confidence: 99%